Localization of Symbiotic Clostridia in the Mixed Segment of the Termite Nasutitermes takasagoensis (Shiraki) - Tokuda, Gaku (American Society for Microbiology, 2000)
Phylogeny and the distribution of symbiotic bacteria in the mixed segment of the wood-eating termite Nasutitermes takasagoensis (Shiraki) were studied. Bacterial 16S rRNA genes (rDNA) were amplified from the mixed segment of the gut by PCR, and two kinds of sequences were identified. The phylogenetic tree was constructed by neighbor-joining and maximum parsimony methods to identify symbionts harbored in the mixed segment. They are classified as low-G+C-content gram-positive bacteria and are most closely related to the genus Clostridium. The distribution of these bacteria throughout the whole gut was examined by PCR using specific primers, which suggested that they are confined to the mixed segment despite the presence of bacteria throughout the gut. In situ hybridization indicated that the symbiotic bacteria were localized to the ectoperitrophic space between the midgut wall and the peritrophic membrane in the mixed segment. Electron microscopy revealed the close association between these bacteria and the mesenteric epithelium, suggesting that they have some interactions with the gut tissue of termites.